2018
DOI: 10.1016/j.whi.2017.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Abortion Service Delivery in Hostile, Middle-ground, and Supportive States in 2014

Abstract: ObjectivesIn 2013, the majority of women lived in states considered hostile to abortion rights, or states with numerous abortion restrictions. By comparison, 31% lived in supportive states. This study examined differences in abortion service delivery according to the policy climate in which clinics must operate.MethodsData come from the 2014 Abortion Provider Census, which contains information about all known abortion-providing facilities in the United States. In addition to number and type of facility, we exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(39 citation statements)
references
References 16 publications
2
37
0
Order By: Relevance
“…27 The majority of patients obtaining abortions are poor or low-income, many lack health insurance that will cover the procedure, 28 and many live in states with numerous abortion restrictions. 8 These factors, along with the increased accessibility of resources to help individuals safely self-manage their abortions outside of a clinical setting, likely account for some of the decline in abortions that we have documented. However, one national survey of U.S. adult women, conducted in 2017, found that only 1.4% reported ever having attempted to end a pregnancy on their own.…”
Section: Changes In Clinic Numbers Abortion Rates and Policy Contextmentioning
confidence: 92%
See 1 more Smart Citation
“…27 The majority of patients obtaining abortions are poor or low-income, many lack health insurance that will cover the procedure, 28 and many live in states with numerous abortion restrictions. 8 These factors, along with the increased accessibility of resources to help individuals safely self-manage their abortions outside of a clinical setting, likely account for some of the decline in abortions that we have documented. However, one national survey of U.S. adult women, conducted in 2017, found that only 1.4% reported ever having attempted to end a pregnancy on their own.…”
Section: Changes In Clinic Numbers Abortion Rates and Policy Contextmentioning
confidence: 92%
“…These declines were steepest in the Midwest and South (22% and 13%, respectively), regions that had also enacted the most abortion restrictions. 8 Still, the 2014 study did not identify a clear association between changes in clinic numbers and state abortion rates between 2011 and 2014; for example, the declines in abortion rates in some states that had lost one-third or more of their clinic facilities mirrored, or were smaller than, the national decline. Updated national data suggest that the overall number of facilities providing abortion did not change much between 2014 1 and 2017, 9 but state and regional patterns of clinic closures may reveal meaningful patterns in availability of and access to services over time.…”
mentioning
confidence: 96%
“…Ten of the top 25 health systems in the US are Catholic, furthermore, one in six beds are now in Catholic hospitals [ 1 ]. The historically non-religious Washington State, deemed a state with a supportive abortion policy environment [ 2 ], has been particularly impacted by this shift, where 34% of the hospitals and 40% of the hospital beds are located in Catholic affiliated hospitals – greater than the national average [ 1 ]. This trend of increasing hospital care falling under Catholic jurisdiction is predicted to continue [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…Between 2008 and 2014, U.S. abortion rates fell by about 25%, with declines largest among teens (46%; Jones & Jerman, ). The decrease in abortions is attributable both to less demand (fewer unintended pregnancies) and less supply as a result of the growing number of state‐level restrictions limiting access to abortion (Foster, ; Jones, Ingerick, & Jerman, ). Such restrictions include requirements about physician admitting privileges, mandatory counseling, waiting periods, facility standards, and gestational limits.…”
Section: Levels Trends and Patterns In Childbearingmentioning
confidence: 99%